Analisis Pelaksanaan Penanganan Dan Pencegahan Corona Virus Disease19 di Kecamatan Plaju Kota Palembang - Pardosi, Veronika Septiani; Idi, Abdullah; Mardianto, Mardianto (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
This study aims to evaluate the implementation of the Musi Ketupat Activities in Palembang City. This research is a descriptive study with a qualitative approach. The data used are quantitative and qualitative data based on the type, while primary data and secondary data are based on the source. The data collection instruments used were observation, interview and documentation. The informants in this study were the Director of Traffic of the South Sumatra Regional Police, the Musi Ketupat Activities Executive Officers in Palembang City, the Head of the Operational Section of the Palembang City Transportation Service, the Palembang City Community. Data analysis is a qualitative analysis with an interactive model. Based on the results of the study, it can be concluded that the implementation of the Musi Ketupat Activity in Palembang City has been carried out in order to enforce the ban on Eid homecoming to prevent the spread of the Covid-19 virus.